Eksplorasi Motif dan Kepuasan Pengguna dalam Mengonsumsi Konten Edukasi Kesehatan: Studi Uses and Gratifications pada Akun TikTok @dr.incognito_99 - Herfriady, Herfriady; Dewi, Larasati; Saladin, Diany Putri Pratiwi; Pahalmas, Juniior Zamrud (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2026)
This research explores the phenomenon of skincare educational content consumption behavior on new media, specifically the TikTok account @dr.incognito_99, which serves as a primary reference for audiences amidst the surge of beauty trends and the risks of digital misinformation. The objective of this study is to describe the phenomenological experiences of the audience, analyze their interpretation of messages, and uncover the impact of such content on consumptive behavior and skincare routines. Utilizing a qualitative method with a phenomenological approach and the Uses and Gratifications Theory framework, this study involved five active Gen Z informants through in-depth interviews and observations. The findings indicate that the audience acts as active agents who consciously select content to satisfy cognitive (medical information) and affective (entertainment) gratifications. Dr. Abelina’s professional credibility as a medical practitioner serves as the primary pillar triggering a transformation in digital health literacy, where audiences deconstruct viral marketing narratives. Key results reveal a shift from impulsive, trend-based consumption to rational decision-making grounded in the analysis of active ingredients and product functionality. The study concludes that the @dr.incognito_99 account has successfully reconfigured TikTok from an entertainment-centric platform into a credible medical education space, significantly impacting the audience's self-care routines in accordance with health standards. These implications underscore the necessity of professional medical presence on social media as knowledge mediators to foster a more literate and responsible digital society.